Tren Glow Up Challenge di Masa Pandemi Covid-19 - Rahma Rahma; Nurul Ilmi Idrus (Universitas Muslim Maros, 2022)
The implementation of large-scale social restrictions (PSBB) by the government as an effort to prevent the transmission of the Corona virus has caused a shift in community activities. Many get bored while staying at home and using social media to entertain themselves. One of the most widely used social media during the pandemic is TikTok application. Lots of interesting content uploaded on TikTok which later became a trending activity, one of which is the trend of Glow Up Challenge. This article explores this trend. This research was conducted virtually, namely on TikTok social media because TikTok was booming during the Covid-19 pandemic and was used to follow this trend by uploading their videos with the hashtag #glowupchallenge. Data was collected using in-depth interview and observation. Interviews were conducted online using the Whatsapp application in the form of chat and voicenotes to find out students' perceptions of the Glow Up Challenge trend, the reasons why many millennials and Generation Z are following this trend, and the impact of this trend on their lives. Observations were made through website that discussed the Glow Up Challenge trend and videos using #glowupchallenge through TikTok social media as well as the appeared comments. The fourteen informants involved in this study were generation Z who observed trend Glow Up Challenge. They are students from various universities in the city of Makassar and outside Makassar, consisting of ten women and four men. The study indicates that the trend Glow Up Challenge is a trend where someone uploads videos that show physical changes in TikTok application. Those who participated in the Glow Up Challenge trend because they were aimed to change their physical appearance for their self confidence; to show others who underestimated them because of their physical appearance that is not in accordance with